2010
DOI: 10.1097/tp.0b013e3181c5cdc1
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Survival Following Liver Transplantation in Infants: A Single-Center Analysis of More Than 200 Cases

Abstract: Background Infants (<12 months) who require liver transplantation (LTx) represent a particularly challenging and understudied group of patients. Methods This retrospective study aimed to describe a large single center experience of infants who received isolated LTx, illustrate important differences in infants vs. older children, and identify pre-transplant factors which influence survival. Over 25 pre-LTx demographic, laboratory, and operative variables were analyzed using the Log-Rank Test and Cox Proportio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
71
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(81 citation statements)
references
References 57 publications
9
71
1
Order By: Relevance
“…( Moreover, in comparison to other age groups, children below-1-year-old had the lowest survival rate, which is in agreement with other studies, including the one performed by Venick; however, this finding had no significant effect in the Cox model (19, 20). Similar to most previous studies, Wilson’s disease and biliary atresia were the most prevalent indications leading to transplantation in the present study (8, 16).…”
Section: Discussionsupporting
confidence: 90%
“…( Moreover, in comparison to other age groups, children below-1-year-old had the lowest survival rate, which is in agreement with other studies, including the one performed by Venick; however, this finding had no significant effect in the Cox model (19, 20). Similar to most previous studies, Wilson’s disease and biliary atresia were the most prevalent indications leading to transplantation in the present study (8, 16).…”
Section: Discussionsupporting
confidence: 90%
“…Recently, Venick et al (17) reported that the 1, 5, and 10 yr graft survival rates under 12 months of age were 75%, 72%, and the patient survival rates 68% and 79%, 77%, and 75%, respectively. Their report concluded that, compared to older recipients, small infants showed poorer survival outcome.…”
Section: Discussionmentioning
confidence: 99%
“…I mprovements in surgical techniques and perioperative care as well as optimization of immunosuppressive medications have led to excellent rates of patient and graft survivals after pediatric liver transplantation (LT), almost independent of the recipient's age. 1,2 It is now important to focus on improving long-term outcomes for pediatric transplant recipients. The immune mechanisms that lead to chronic allograft dysfunction are still not clearly defined, but there is increasing evidence that mismatching of anti-HLA antibodies and the presence of anti-donor specific antibodies (DSA) may adversely impact long-term graft survival.…”
mentioning
confidence: 99%